Best classroom management practices for reaching all learners : what award-winning classroom teachers do - Stone, Randi (Thousand Oaks, Calif. : Corwin Press, 2005)
Do you enjoy swapping ideas with other teachers? Do you find the staffroom is the best place to learn? Do you wish you had time to attend classroom management seminars? The exchange of ideas often allows teachers to fine tune strategies for managing their classrooms by listening to others who have successfully overcome similar challenges. This inspiring collection of advice from award-winning teachers now brings the best of classroom management practice to your classroom. Best Classroom Management Practices for Reaching All Learners compiles strategies, suggestions, tactics, and plans for improving classroom management approaches. By observing the best run classrooms through the eyes of our best teachers, Stone brings us solutions to teachers' everyday questions and issues. learning experiences in today's diverse classrooms by covering such topics as: Building classroom community, working with challenging students, and communicating with parents; Rules, rewards, discipline, silence, and shared responsibilities; Homework, posters, newsletters, and reading groups; Computer labs and classroom technology; Invite Randi Stone and 29 expert educators into your classroom and find a virtual staffroom at your fingertips!
Keywords: Classroom management -- United States; Classroom management